2017
DOI: 10.1111/ajt.13998
|View full text |Cite
|
Sign up to set email alerts
|

Early Macrophage Infiltration and Sustained Inflammation in Kidneys From Deceased Donors Are Associated With Long-Term Renal Function

Abstract: Kidney transplants from living donors (LDs) have a better outcome than those from deceased donors (DDs). Different factors have been suggested to justify the different outcome. In this study, we analyzed the infiltration and phenotype of monocytes/macrophages and the expression of inflammatory and fibrotic markers in renal biopsy specimens from 94 kidney recipients (60 DDs and 34 LDs) at baseline and 4 months after transplantation. We evaluated their association with medium- and long-term renal function. At ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Dias et al found that CD68 was associated with the progression of chronic kidney disease in 50 patients with proliferative LN by immunohistochemical analysis (24). Guillén-Gómez et al found that a large number of CD68-positive cells in the kidneys were negatively associated with long-term renal function (25), which was consistent with the results of the present study. TGF-β is a 25 kDa homodimer prototype of the protein family that regulate cell growth and differentiation, which can stimulate and inhibit cell growth, and is considered to be the main switch in the pathogenesis of organ fibrosis (26).…”
Section: Discussionsupporting
confidence: 91%
“…Dias et al found that CD68 was associated with the progression of chronic kidney disease in 50 patients with proliferative LN by immunohistochemical analysis (24). Guillén-Gómez et al found that a large number of CD68-positive cells in the kidneys were negatively associated with long-term renal function (25), which was consistent with the results of the present study. TGF-β is a 25 kDa homodimer prototype of the protein family that regulate cell growth and differentiation, which can stimulate and inhibit cell growth, and is considered to be the main switch in the pathogenesis of organ fibrosis (26).…”
Section: Discussionsupporting
confidence: 91%
“…12 Moreover, macrophage infiltration is also associated with poor long-term eGFR behavior in kidneys from deceased but not from living donors, thus confirming a potential role of early inflammation in the risk of subsequent CKD in KTRs after transplantation, and somewhat explaining the better outcome observed in KTRs receiving kidneys from living donors. 13 Another important finding of our study is that in our patients early and severe macrophage infiltration proved to be even more predictive of subsequent graft loss than early IFTA, which characterizes chronic kidney allograft dysfunction and usually develops before any significant clinical evidence of graft damage appears. 14 The last finding of this study is that macrophage infiltration actually proved to be even superior than de novo DSA in predicting subsequent graft loss.…”
Section: Discussionsupporting
confidence: 49%
“…Early macrophage graft infiltration and graft inflammation are associated with poor kidney transplant outcomes ( 54 ). Data in Figure 6B reveal a significant reduction in early (d3) macrophage graft infiltration in Axl -KO recipients in comparison with WT recipients.…”
Section: Resultsmentioning
confidence: 99%